(untitled) (European Journal of Mental Health, 2010)
Charitable Activities of Hungarian Historical Christian Churches during Communism, and Their Effects on Post-Communist Charitable Church Activities, Part 1: In addition to assessing charitable activities of Hungarian historical Christian churches during communism from a fact-finding, descriptive angle, this two-part study also provides a view of what effects this has on post-communist charitable church activities. Understandably, this necessitates a brief overview of the types and volume of charitable activities carried out by the catholic, reformed and evangelical churches prior to the communist power grab. In the years following the Second World War, the majority of social institutions run by the church came under state control, with new employees often looking upon the tasks they were to carry out only as a way of making a living, and lacking a commitment to the service they were to perform. The way in which state socialist politics strove to use charity and diaconate in their efforts aimed at wasting church and faith can be clearly observed. The measures, according to which practically only institutions where missionary work was impossible or possible only to a minor degree could remain in church hands, also served this end. Church leaders who tried to ensure survival by adhering to the official line, also partly became partners to the state. It is considered a step forward, when badly paid positions requiring hard work and commitment at social institutions run by the state were filled by qualified and able labour based on church recommendations and nominations. During the period of dictatorship, charitable activities by congregations and parishes also experienced a strong setback. Following the collapse of communism, all three churches displayed an intention of reviving their charitable activities by maintaining spirituality and charisma despite a necessary institutionalisation process and strict professionalism. The analysis also pinpoints some cases that highlight the pitfalls of relations with the post-communist state. The first half of the study presents the operation of helping services linked to protestant churches, with the reformed and evangelical churches discussed separately. The second part provides an overview of the conditions of catholic charity during the years of dictatorship, using similar considerations, and also has a look at the times before the Second World War and the changed circumstances following the 1989 fall of communism.